RESISTANCE OF RED CURLY CHILI (Capsicum annuum L.) SPROUTS TO FUSARIUM OXYSPORUM INFECTION FROM SEEDS INDUCED BY 0.2 mT - Essy Dumayanti; Rochmah Agustrina; Wawan Abdullah Setiawan; Eti Ernawiati; Yulianty Yulianty; Lili Chrisnawati (Jurnal Ilmiah Biologi Eksperimen dan Keanekaragaman Hayati (J-BEKH), 2021)
Curly red chili (Capsicum annuum L.) is widely used as industrial raw material because it has a spicy taste. The increasing demand for chili is not balanced with the level of production. Chilies are susceptible to disease, one of which is fusarium wilt. The magnetic field affected the physical and chemical properties of water so that it increased peroxidase enzyme activity and plant metabolism. This research was aim to know the protective effect seeds induced by 0.2 mT Magnetic Fiel had given to red curly chili (Capsicum annuum L.) sprouts to Fusarium oxysporum infection. This study was arranged in a completely randomized design (CRD) with 5 treatments consisting of M0F0 (control), M7F0, M7F60, M15F0, M15F60. M0 is a seed not induced by a magnetic field; M7 is seed induced by magnetic field 7 minutes 48 seconds, M15 is seed induced by magnetic field 15 minutes 36 seconds, F0 is sprouted not infected with F. oxysporum and F60 is sprouts infected with F. oxysporum for 60 minutes. Each unit is repeated 5 times. The results of the ANOVA showed that exposure to a magnetic field had a significant effect on increasing plant height at 21, 28, and 35 days after planting (HST); the wet and dry weight of 7 days old plants; and the content of chlorophyll a, b, and total before flowering 21 days after planting. Overall, the 0.2 mT magnetic field treatment for 7 minutes 48 seconds tended to give better results to increase the growth of chili plants against F. oxysporum infection.